Karakteristik Amilografi Tepung Jagung Termodifikasi dengan Fermentasi Spontan dan Perendaman dalam Larutan Kalsium Hidroksida - Tjahja Muhandri; Papang Sulton Nularif; Dase Hunaefi (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2016)
The research was aimed to study the effect of spontaneous fermentation and soaking in 1% (w/v) calcium hydroxide (Ca(OH)2) of the corn grits (cultivar varieties of P21) on the yield of corn flour and its pasting properties. Spontaneous fermentation with the ratio water to grits of 3 : 1 was conducted in a closed container for 12, 24, 48, and 72 hours, while the soaking treatment in a solution of 1% (w/v) Ca(OH)2 was performed for 1, 2, and 3 hours with the ratio solution to the grits of 2:1. The results showed that spontaneous fermentation and soaking in a solution of Ca(OH)2 of corn grits increased the yield and peak viscosity of corn flour. Those treatments also decreased the initial gelatinization tempe-rature, maximum gelatinization temperature, viscosity breakdown and retrogradation of the corn flour.